QUALITY EVALUATION OF CHICKEN SAUSAGES FROM SPENT BROILER BREEDER HENS DURING FROZEN STORAGE - J. Indumathi; M. Shashikumar; G.V. Bhaskar Reddy; A. Jagadeesh Babu; M. Gnanaprakash (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The current study was designed to evaluate the influence of three different ground vegetable oil seeds on various physico-chemical, microbiological and sensory attributes of chicken sausages from spent broiler breeder hen stored under frozen (-18±1°C) condition. Chicken sausages were incorporated with ground poppy, sesame and peanut seeds each at 10 % level separately as three treatments and were analyzed for their keeping quality along with high fat control. The mean values of FFA, TBARS, tyrosine values, standard plate count, psychrophilic count and yeast and moulds counts were significantly (P